In Situ Generation of Fullerene from a Poly(fullerene) - Silva, Hugo Santos (2019)
This article appraises the thermal, photo- and photo-oxidative stability of poly(fullerene)-alt-[bismethylbenzene)]s (PFBMBs) prepared by the atom transfer radical addition polymerization (ATRAP) with particular attention paid to their use as additives in organic photovoltaic devices. PFBMBs are of interest due to their well-defined structures based on alternating, main-chain, fullerene-methylene links. This work shows by way of a wide range of characterization techniques and a small library of PFBMBs with varying side chains, however, that PFBMBs are relatively unstable. Given that prior work has shown that other main-chain fullerene polymers, such as poly(pyrrolidinofullerene)s, are inherently stable, we suggest a degradation mechanism specific to the fullerene-methylene links of PFBMBs, which explains their unusual behavior. This work suggests that polymers based on fullerene each have their own specific stabilities and qualities and that PFBMBs might be of more use in purposes other than OPVs where in situ delivery of fullerene is required, for example, in medical applications. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2019, 57, 1434–1452.